Information Re-Retrieval: Repeat Queries in Yahoo's Logs - Teevan, Jaime; Adar, Eytan; Jones, Rosie; Potts, Michael (Proceedings of the 30th Annual ACM Conference on Research and Development in Information Retrieval (SIGIR 2007), Amsterdam, The Netherlands, 2007)
People often repeat Web searches, both to find new information on topics they have previously explored and to re-find information they have seen in the past. The query associated with a repeat search may differ from the initial query but can nonetheless lead to clicks on the same results. This paper explores repeat search behavior through the analysis of a one-year Web query log of 114 anonymous users and a separate controlled survey of an additional 119 volunteers. Our study demonstrates that as many as 40% of all queries are re-finding queries. Re-finding appears to be an important behavior for search engines to explicitly support, and we explore how this can be done. We demonstrate that changes to search engine results can hinder re-finding, and provide a way to automatically detect repeat searches and predict repeat clicks.